THE DEVELOPMENT OF ISLAMIC SOCIETY BASED ON CELESTIAL BUSINESS - Agus Ahmad Safei (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2016)
Empirically, Islamic society in Indonesia —as the majority of the population— hasnot been able to compete with the various advantages possessed by Islamic societies in other countries, particularly in the developed ones. Academically, the conceptual references on the development of Islamic society are relatively hard to find. These facts warrant both empirical and academic efforts to develop the concepts and formulas of Islamic society development, especially regarding its economical aspect. This report will further describe the importance of a formula for developing Islamic society, based on celestial business (al-mubaya’ah al-samawiyah), and how it can be a solution to the problem of economical dis¬advantages in Islamic societies. This research used literary method that conducted by analyzing various literatures relevant with the topic of the research. The findings show that conceptually, the celestial business (business with God) formula is relevant for the development of the economic aspect of Islamic societies. This formula offers equilibrium between the satisfaction of material and spiritual needs, or the physical and spiritual needs. On the higher level, it can be an alternative formula to develop the economic aspect of any Islamic society.